Masked face is looking at me: Face mask increases the feeling of being looked at during the COVID-19 pandemic - Liu, Jiakun; Yang, Jiajia; Huang, Lihui; Zhou, Li; Xie, Jinxi; Hu, Zhonghua (Frontiers in Neuroscience, 2022)
As the COVID-19 global pandemic unfolded, governments recommended wearing face masks as a protective measure. Recent studies have found that a face mask influences perception; but how it affects social perception, especially the judgment of being looked at, is still unknown. This study investigated how wearing a mask influences the judgment of gaze direction by conducting a cone of direct gaze (CoDG) task. In Experiment 1, three types of masked faces were considered to investigate whether the effect of masks on CoDG is modulated by mask types. The results found that wearing masks widens the CoDG, irrespective of the mask type. Experiment 2 replicated the results of Experiment 1 by adding a learning phase to help participants better distinguish N95-mask and surgical mask. Furthermore, to investigate whether the effect of masks derives from its social significance, a face with only the eye-region (a mouth-cut face) was used as the stimuli in Experiment 3. The results found the CoDG of N95-mask wearing faces to be wider than the mouth-cut and non-masked faces. The results also indicated no significant difference between the CoDG of mouth-cut and non-masked faces, illustrating that the influence of wearing masks on CoDG was due to high-level social significance rather than low-level facial feature information. In addition, the results of questionnaires showed that the frequency at which individuals wore masks during the novel coronavirus pandemic may have reduced the impact of masks on the CoDG. The present findings are of great significance for understanding the impact of wearing masks on human social cognition in the context of COVID-19.